Assessment of the protection system in response to different grid-tied converters - Xu, Zhi; Alimasibieke, Shakenbieke; Zhai, Baoyu; Yang, Qi; Wang, Yuchen (Frontiers in Energy Research, 2023)
The power system is migrating to 100% penetration of the converter-interfaced generation (CIG). The grid-forming converter-based CIG has been proposed to be a solution to replace the synchronous generation (SG) in order to form the grid and achieve the 100% penetration target. However, besides the generation, whether the protection system can coordinate this transition is still an open question. Although the grid-forming converter operates as the same manner as the SG, unlike SG, it physically has constraints on its current output which in transient leads to different operation to the SG. This paper aims to investigate whether these different transients have effects on the protection system, specifically, investigate if the protection system remains reliable when the system migrates to 100% penetration. The investigation is based on the hardware in-the-loop experiment, considering different converter control, different type of the fault, different length of the line and different fault location. The result shows that the grid-forming converter has a reliable coordination with the protection system in response to the fault.